2014
DOI: 10.1016/j.bbamem.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Structure-dependent interactions of polyphenols with a biomimetic membrane system

Abstract: Polyphenols are naturally-occurring compounds, reported to be biologically active, and through their interactions with cell membranes. Although association of the polyphenols with the bilayer has been reported, the detailed mechanism of interaction is not yet well elucidated. We report on spatio-temporal real-time membrane dynamics observed in the presence of polyphenols. Two distinct membrane dynamics, corresponding to the two classes of polyphenols used, were observed. Flavonoids (epi-gallocatechin-3-gallate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 40 publications
7
67
0
Order By: Relevance
“…Studies have shown that flavonoids carry hydrogen bonds with the polar heads of the cell membrane phospholipids; as the polarity increases, the flavonoid interaction becomes more intense. These interactions promote greater aggregation of the phospholipids, thus reducing the membrane fluidity parameter (Phan et al., ; Wu et al., ). As anthocyanins are high‐polarity flavonoids, evidenced by the hydrophilic characteristic of this subclass of compounds, erythrocytes are protected from hypotonic hemolysis by red chicory extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that flavonoids carry hydrogen bonds with the polar heads of the cell membrane phospholipids; as the polarity increases, the flavonoid interaction becomes more intense. These interactions promote greater aggregation of the phospholipids, thus reducing the membrane fluidity parameter (Phan et al., ; Wu et al., ). As anthocyanins are high‐polarity flavonoids, evidenced by the hydrophilic characteristic of this subclass of compounds, erythrocytes are protected from hypotonic hemolysis by red chicory extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Biochanin A is known as strong scavenger of ROS, activator of SOD (superoxide dismutase) enzyme activity and reducer of COX-2 expression [31]. However, there is growing evidence of polyphenols' reactions with nonpolar compounds present in the hydrophobic inner membrane layer [18,32,33]. Thus, the second way of protection of the cellular Control cells were not exposed to any compound but the vehicle; values are means ± standard deviations from at least three independent experiments; statistical significance was calculated versus control cells (untreated); *** p ≤ 0.001.…”
Section: Trifolium Pratense L As a Chemopreventive Agentmentioning
confidence: 99%
“…And we speculate that the plasma membrane damage induced by PC-EEF may relate 25 to the interactions between PC-EEF with the membrane system (Phan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%